2002
DOI: 10.2466/pms.2002.95.3f.1199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Appropriate and Inappropriate Odors on Product Evaluations

Abstract: In accounting for an odorant's effect on the evaluation of a product, both the odor's intrinsic pleasantness and its appropriateness for that particular product are relevant. When comparing the effects of pleasant smells, consumers are likely to prefer products with appropriate smells to those with an inappropriate smell. We investigated the effect of adding congruent and incongruent odorants on product evaluations for each of three product categories: food (tea, instant whip, cake mix), personal care (shampoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These results are in line with those observed in the literature, these different information influences having already been described for specific sensory perceptions (Schifferstein, 2002;Tuorila et al, 1994;Zellner, Bartoli, & Eckard, 1991), for traditional liking assessments (Cardello & Sawyer, 1992;Tuorila et al, 1994; see also the review from Deliza & MacFie, 1996), and for product experience (Schifferstein, 2009). More specifically in the olfaction field, various studies have also demonstrated the influence of name context on olfactory perception in terms of sensory perception and pleasantness (Distel & Hudson, 2001;Distel et al, 1999;Moskowitz, 1979).…”
Section: Discussionsupporting
confidence: 84%
“…These results are in line with those observed in the literature, these different information influences having already been described for specific sensory perceptions (Schifferstein, 2002;Tuorila et al, 1994;Zellner, Bartoli, & Eckard, 1991), for traditional liking assessments (Cardello & Sawyer, 1992;Tuorila et al, 1994; see also the review from Deliza & MacFie, 1996), and for product experience (Schifferstein, 2009). More specifically in the olfaction field, various studies have also demonstrated the influence of name context on olfactory perception in terms of sensory perception and pleasantness (Distel & Hudson, 2001;Distel et al, 1999;Moskowitz, 1979).…”
Section: Discussionsupporting
confidence: 84%
“…Pleasant odors have also been demonstrated to affect buying (see Bone & Ellen, 1999;also Hirsch, 1995;Mitchell, Kahn, & Knasko, 1995;Spangenberg, Crowley, & Henderson, 1996). However, this is only the case if the smell fits the product (Schifferstein & Michaut, 2002).…”
Section: Integrationmentioning
confidence: 99%
“…Finding no effect of matching is not uncommon in studies involving smells. For instance, Schifferstein and Michaut (2002) investigated the effect of adding congruent or incongruent pleasant odors on product evaluations for food, personal care and household products. These authors also found no effect of the degree of odor-product congruency on overall product evaluations and buying intentions.…”
Section: Resultsmentioning
confidence: 99%